Epitaxial Ultrathin Films: Atomic‐Scale Metal–Insulator Transition in SrRuO3 Ultrathin Films Triggered by Surface Termination Conversion (Adv. Mater. 8/2020). Issue 8 (24th February 2020) - Lee, Han Gyeol; Wang, Lingfei; Si, Liang; He, Xiaoyue; Porter, Daniel G.; Kim, Jeong Rae; Ko, Eun Kyo; Kim, Jinkwon; Park, Sung Min; Kim, Bongju; Wee, Andrew Thye Shen; Bombardi, Alessandro; et al.
Abstract : In article 1905815, Lingfei Wang, Tae Won Noh, and co‐workers simply utilize water‐leaching to realize an atomic‐scale structural modulation at the surface of SrRuO3 epitaxial film: the surface termination converts from SrO to RuO2 . The resultant changes in crystal‐field symmetry and orbital occupancy stabilize a one‐unit‐cell‐thin insulating surface state in this prototypical metallic oxide.